Validity of Self‐Reported Pre‐Pregnancy Weight and Body Mass Index Classification in an Integrated Health Care Delivery System. Issue 4 (9th March 2016) - Han, Emily; Abrams, Barbara; Sridhar, Sneha; Xu, Fei; Hedderson, Monique
Abstract: Background: Self‐reported weight prior to pregnancy is prone to error. We utilised a measured pre‐conceptional weight from the electronic health record (EHR) to investigate error in recalled pre‐pregnancy body mass index (BMI) category and compared how associations between pre‐pregnancy BMI and pregnancy outcomes varied by using the two measures. Methods: We assessed differences in means, correlations, and categorisation of pre‐pregnancy BMI for 5092 singleton pregnancies delivered between 2007 and 2013 in Kaiser Permanente Northern California. Associations between measured and self‐reported BMI category and gestational diabetes, infant size for gestational age, and exceeding the Institute of Medicine gestational weight gain recommendations were assessed. Results: Overall, the two measures assigned the same BMI category for 86.7% of women with higher risks of misclassification for overweight (Relative Risk (RR) 3.38, 95% Confidence Interval (CI) 2.79, 4.10), obese class I (RR 3.81, 95% CI 3.07, 4.75), and obese class II (RR 1.80, 95% CI 1.28, 2.55) women compared to normal weight women. However, associations between self‐reported or measured BMI category and several pregnancy outcomes were similar. Conclusions: Despite misclassification, self‐reported and measured pre‐pregnancy weights were similarly associated with perinatal outcomes in this study population. Our results illustrate the value of the EHR for recording measured pre‐pregnancy weight for use in research.